Rates of human–macaque interactions affect grooming behavior among urban‐dwelling rhesus macaques (Macaca mulatta). Issue 1 (3rd October 2018) - Kaburu, Stefano S. K.; Marty, Pascal R.; Beisner, Brianne; Balasubramaniam, Krishna N.; Bliss‐Moreau, Eliza; Kaur, Kawaljit; Mohan, Lalit; McCowan, Brenda
Abstract: Objectives: The impact of anthropogenic environmental changes may impose strong pressures on the behavioral flexibility of free‐ranging animals. Here, we examine whether rates of interactions with humans had both a direct and indirect influence on the duration and distribution of social grooming in commensal rhesus macaques ( Macaca mulatta ). Materials and Methods: Data were collected in two locations in the city of Shimla in northern India: an urban setting and a temple area. We divided these two locations in a series of similar‐sized physical blocks ( N = 48) with varying rates of human–macaque interactions. We conducted focal observations on three free‐ranging rhesus macaque groups, one in the urban area and two in the temple area. Results: Our analysis shows that macaques engaged in shorter grooming bouts and were more vigilant while grooming in focal sessions during which they interacted with people more frequently, suggesting that humans directly affected grooming effort and vigilance behavior. Furthermore, we found that in blocks characterized by higher rates of human–macaque interactions grooming bouts were shorter, more frequently interrupted by vigilance behavior, and were less frequently reciprocated. Discussion: Our work shows that the rates of human–macaque interaction had both a direct and indirect impact on grooming behavior and that macaques flexibly modified their grooming interactions in relation to the rates of human–macaque interaction to which they were exposed. Because grooming has important social and hygienic functions in nonhuman primates, our work suggests that human presence can have important implications for animal health, social relationships and, ultimately, fitness. Our results point to the need of areas away from people even for highly adaptable species where they can engage in social interactions without human disruption.